Variation in grain productivity and quality of modern winter wheat varieties in northern Ukrainian Steppe - Назаренко, Микола Миколайович; Nazarenko, Mykola; Миколенко, Світлана Юріївна; Mykolenko, Svitlana; Охмат, Петро; Okhmat, Petro (Мелітопольский державний педагогічний університет ім. Богдана Хмельницкого, 2020)
We have been studying the grain productivity and quality of 22 new winter wheat varieties during three years under North Ukrainian Steppe conditions. These 22 winter wheat varieties and control (national standard by grain productivity variety Podolyanka) were investigated regarding their interactions with environmental conditions by agronomic-value traits like as general grain productivity, components of one, protein and gluten content, developing relations between once (correlation relations), which determining wheat quality and yield in a complex. Two high-adaptive varieties Divo and Matrix, which provides us higher than standard grain yield in complex with higher or proper protein and gluten content were developed. Two factors permanently influenced on grain productivity (conditions of the year and genotype), while only one (genotype) determined the protein content of grains. We used the weight of thousand grains as an integrative parameter of the yield structure for all productive varieties, with no regards to yield formation.
Відмінності в урожайності зерна та якість сучасних сортів озимої пшениці в північному степу України
Keywords: озима пшениця; Winter wheat; різноманітність; Variety; урожайність зерна; Grain productivity; зерновий білок; Grain protein